2007
DOI: 10.1007/bf03349237
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status among pregnant women in Kuwait

Abstract: Data obtained may indicate insufficient iodine intake among pregnant women in Kuwait.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…As a result, the effect of age of TSH testing in an iodine-deficient region and the use of neonatal TSH values to assess iodine nutrition have not been systematically previously evaluated. Previous observations in Ethiopia (18) Sicily (19), Argentina (12), Kuwait (20), Turkey (21), Nepal (22), and Thailand 23, all of which have populations that experience iodine deficiency, are consistent with the findings reported here. A recent report on iodine intake and neonatal TSH values in Ireland, an iodine sufficient region, concluded that the trend in the mean TSH value of a population that has adequate iodine intake is a more sensitive indicator of changes in iodine intake than the % of TSH values >5 mIU/L (24).…”
Section: Discussionsupporting
confidence: 92%
“…As a result, the effect of age of TSH testing in an iodine-deficient region and the use of neonatal TSH values to assess iodine nutrition have not been systematically previously evaluated. Previous observations in Ethiopia (18) Sicily (19), Argentina (12), Kuwait (20), Turkey (21), Nepal (22), and Thailand 23, all of which have populations that experience iodine deficiency, are consistent with the findings reported here. A recent report on iodine intake and neonatal TSH values in Ireland, an iodine sufficient region, concluded that the trend in the mean TSH value of a population that has adequate iodine intake is a more sensitive indicator of changes in iodine intake than the % of TSH values >5 mIU/L (24).…”
Section: Discussionsupporting
confidence: 92%
“…Suboptimal iodine status has been reported in pregnant women from areas with only partial house-hold coverage with iodized salts such as Italy, Kuwait, and India. [ 8 9 10 11 ] Even though our study confirms those previous findings, countries with long-standing successful iodized salt programs have reported an optimal median UIC in pregnant women. [ 12 ]…”
Section: Discussionsupporting
confidence: 89%
“…Several recent studies have suggested suboptimal iodine status in pregnant women from areas with only partial household coverage with iodized salt, such as Italy, India, and the US (8)(9)(10)(11)(12). Our study confirms these previous findings and demonstrates a similar relationship within families eating from the same household food basket.…”
Section: Discussionmentioning
confidence: 99%
“…Most national or subnational IDD surveys have been conducted in school-aged children (7) and if the median UI in school-aged children is 100-199 mg/L, it is generally assumed that all population groups, including pregnant women, have adequate iodine nutriture (1). However, recent cross-sectional surveys have suggested this assumption may not be valid (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%